Regulatory role of phosphoproteins in the development of bovine small intestine during early life - X.W. Zhao; H.L. Zhu; Y.X. Qi; T. Wu; D.W. Huang; G.L. Cheng; Y.X. Yang; D.P. Bu; H. Hu; L.F. Meng (Journal of Dairy Science, 2022)
ABSTRACT: The small intestine is the primary site of nutrient digestion and absorption, which plays a key role in the survival of neonatal calves. A comprehensive assessment of the phosphoproteomic changes in the small intestine of neonatal calves is unavailable; therefore, we used phosphopeptide enrichment coupled with liquid chromatography-tandem mass spectrometry to investigate the changes in the phosphoproteome profile in the bovine small intestine during the first 36 h of life. Twelve neonatal male calves were assigned to one of the following groups: (1) calves not fed colostrum and slaughtered approximately 2 h postpartum (n = 3), (2) calves fed colostrum at 1 to 2 h and slaughtered 8 h postpartum (n = 3), (3) calves fed 2 colostrum meals (at 1–2 and 10–12 h) and slaughtered 24 h postpartum (n = 3), (4) calves fed 3 colostrum meals (at 1–2, 10–12, and 22–24 h) and slaughtered 36 h postpartum (n = 3). Mid-duodenal, jejunal, and ileal samples of the calves were collected after slaughter. We identified 1,678 phosphoproteins with approximately 3,080 phosphosites, which were mainly Ser (89.9%), Thr (9.8%), and Tyr (0.3%) residues; they belonged to the prodirected (52.9%), basic (20.4%), acidic (16.6%), and Tyr-directed (1.7%) motif categories. The regional differentially expressed phosphoproteins included zonula occludens 2, sorting nexin 12, and protein kinase C, which are mainly associated with developmental processes, intracellular transport, vesicle-mediated transport, and immune system process. They are enriched in the endocytosis, tight junction, insulin signaling, and focal adhesion pathways. The temporal differentially expressed phosphoproteins included occludin, epsin 1, and bridging integrator 1, which were mainly associated with macromolecule metabolic process, cell adhesion, and growth. They were enriched in the spliceosomes, adherens junctions, and tight junctions. The observed changes in the phosphoproteins in the tissues of small intestine suggest the protein phosphorylation plays an important role in nutrient transport and immune response of calves during early life, which needs to be confirmed in a larger study.